Relationship between permanent maxillary canine and floor of the maxillary sinus through aging (Mustansiria Dental Journal, 2018)
The maxillary sinus are pyramidal shaped cavities in the mid-facial aspect of theskull; they are bilateral structures, located beside each nasal fossa. Knowledge of therelationship between the root apex and the inferior wall of the maxillary sinus iscrucial for diagnosis and treating a sinus pathosis as well as in assisting dentalimplantation, endodontic procedures and orthodontic treatment. Thirty patientsattending Al-Ma’amoon dental centre were selected in this study according to aspecial criteria. Four digital periapical x –rays were taken for each patient using dentalx – ray machine two views demonstrated both right and left permanent canines tomeasure the length of each tooth by direct double click technique, the other two viewswere taking with concentration on the apical area of each tooth, to measure the exactdistance between the apex of the tooth and the floor of the maxillary sinus. Results ofthis study found that the distance between the apices of right permanent maxillarycanines and the base of maxillary sinus was greater than that of left side and thedistance between the canine apex and the floor of maxillary sinus increasing withincreasing age.